Single-Stage Bilateral Sinusectomy with Methylene Blue Tract Delineation for Familial Classic Preauricular Sinus Following Right-Sided Abscess Control: A Case Report - Jihan Mudrika Rahmi; Al Hafiz (HM Publisher, 2026)
Background. Preauricular sinus is a congenital anomaly arising from incomplete fusion of the auricular hillocks of the first and second branchial arches. The condition shows marked ethnic variation, with bilateral presentations strongly associated with hereditary transmission. Surgical excision remains the only definitive treatment for symptomatic or recurrently infected lesions, yet operative recurrence rates of up to 42% have been historically reported. Case presentation. A 24-year-old Indonesian Minangkabau male presented with bilateral preauricular openings present since birth and a recent right preauricular abscess that had been treated with incision and drainage twenty days prior. His father had a unilateral left-sided preauricular pit, consistent with familial transmission. Examination confirmed bilateral classic-type preauricular fistulae anterior to the ascending helix without active discharge, and a quiescent right post-incision wound. Preoperative blood work, renal and hepatic profiles, and chest radiography were within normal limits. The patient underwent simultaneous bilateral preauricular sinusectomy under general anesthesia using methylene blue tract delineation, elliptical skin incision, complete tract dissection with adjacent granulation removal, and primary closure over a small-calibre drain. Postoperative recovery was uneventful; the drain was removed on day three, sutures were removed on day ten, and the surgical wound remained quiescent without recurrence or hypertrophic scarring at the 39-day follow-up. Conclusion. Simultaneous single-stage bilateral sinusectomy combined with methylene blue tract delineation, prior infection control, and closed-system drainage produced excellent early outcomes in an adult with familial bilateral classic preauricular sinus.